Effect Of Buffalo Bone Charcoal And Baco₃ Composition On The Tensile Strength Of Pack-Carburized Low-Carbon Steel - Yafet Bontong; Ariyen Duri’; Fikran Fikran (Journal of Innovation Research and Knowledge, 2026)
Low-carbon steel has good ductility and formability; however, its relatively low surface hardness and strength limit its application in components requiring improved mechanical performance. One method that can be used to enhance these properties is pack carburizing. This study aims to analyze the effect of varying compositions of buffalo bone charcoal (BBC) and BaCO₃ on the tensile characteristics of low-carbon steel subjected to pack carburizing. The experiment was conducted using three carburizing media compositions: 60% BBC + 40% BaCO₃, 70% BBC + 30% BaCO₃, and 80% BBC + 20% BaCO₃, with a particle size of mesh 20 at temperatures of 850°C and 950°C. The pack carburizing process was carried out with a holding time of 2 hours, followed by normalizing cooling in air. The mechanical characteristics were evaluated based on ultimate tensile strength, elongation, and reduction in cross-sectional area. The results showed that at 850°C, the highest tensile strength was obtained with the composition of 70% BBC + 30% BaCO₃, reaching 1.566,08 MPa. At 950°C, the highest tensile strength was obtained with 80% BBC + 20% BaCO₃, reaching 1.858,93 MPa. Increasing the carburizing temperature from 850°C to 950°C increased the tensile strength for all compositions, with the greatest increase of 62.22% occurring in the 80% BBC + 20% BaCO₃ composition. This condition also exhibited greater deformation based on the elongation and reduction in cross-sectional area. The results indicate that the combination of carburizing media composition and process temperature plays an important role in determining the tensile characteristics of low-carbon steel. Among the investigated conditions, the composition of 80% BBC + 20% BaCO₃ at 950°C produced the best tensile response.